Human Placental Trophoblasts Infected by Listeria monocytogenes Undergo a Pro-Inflammatory Switch Associated With Poor Pregnancy Outcomes - Johnson, Lauren J.; Azari, Siavash; Webb, Amy; Zhang, Xiaoli; Gavrilin, Mikhail A.; Marshall, Joanna M.; Rood, Kara; Seveau, Stephanie (Frontiers in Immunology, 2021)
The placenta controls the growth of the fetus and ensures its immune protection. Key to these functions, the syncytiotrophoblast (SYN) is a syncytium formed by fusion of underlying mononuclear trophoblasts. The SYN covers the placental surface and is bathed in maternal blood to mediate nutritional and waste exchanges between the mother and fetus. The bacterial pathogen Listeria monocytogenes breaches the trophoblast barrier and infects the placental/fetal unit resulting in poor pregnancy outcomes. In this work, we analyzed the L. monocytogenes intracellular lifecycle in primary human trophoblasts. In accordance with previous studies, we found that the SYN is 20-fold more resistant to infection compared to mononuclear trophoblasts, forming a protective barrier to infection at the maternal interface. We show for the first time that this is due to a significant reduction in L. monocytogenes uptake by the SYN rather than inhibition of the bacterial intracellular division or motility. We here report the first transcriptomic analysis of L. monocytogenes-infected trophoblasts (RNA sequencing). Pathway analysis showed that infection upregulated TLR2, NOD-like, and cytosolic DNA sensing pathways, as well as downstream pro-inflammatory circuitry (NF-B, AP-1, IRF4, IRF7) leading to the production of mediators known to elicit the recruitment and activation of maternal leukocytes (IL8, IL6, TNF, MIP-1). Signature genes associated with poor pregnancy outcomes were also upregulated upon infection. Measuring the release of 54 inflammatory mediators confirmed the transcriptomic data and revealed sustained production of tolerogenic factors (IL-27, IL-10, IL-1RA, TSLP) despite infection. Both the SYN and mononuclear trophoblasts produced cytokines, but surprisingly, some cytokines were predominantly produced by the SYN (IL-8, IL-6) or by non-fused trophoblasts (TNF). Collectively, our data support that trophoblasts act as placental gatekeepers that limit and detect L. monocytogenes infection resulting in a pro-inflammatory response, which may contribute to the poor pregnancy outcomes if the pathogen persists.